THE RELATIONSHIP BETWEEN MOTHERS’ KNOWLEDGE AND EDUCATION LEVEL WITH THE MANAGEMENT OF ACUTE RESPIRATORY INFECTIONS (ARI) IN TODDLERS AT BARENG PUBLIC HEALTH CENTER, MALANG CITY - Fitriana, Nikmatul; Milwati, Susi; Wulandari, Lisa Purbawaning (HEARTY, 2026)
Acute Respiratory Infections (ARI) are considered a priority health issue. According to estimates by the World Health Organization (WHO), the incidence of ARI in toddlers in developing countries is 15% - 20% per year. The knowledge and education level of mothers play an important role in independently managing ARI at home, preventing the worsening of the condition. The purpose of this study is to identify the relationship between mothers' knowledge and education level with the management of ARI in toddlers at Bareng Public Health Center. This research design is correlational analytic with a cross-sectional approach. The sample consisted of 80 mothers who had toddlers with ARI and visited the Bareng Public Health Center in Malang City, selected using accidental sampling. Data analysis was performed using the Spearman Rank test and logistic regression test. The results of the Spearman Rank test showed a relationship between knowledge (p-value = 0.000) and education level (p-value = 0.002) of mothers and the management of ARI in toddlers. The logistic regression test results indicated a simultaneous relationship between mothers’ knowledge and education level and the management of ARI in toddlers (significance value = 0.000). It was concluded that mothers’ knowledge and education level affect how they manage ARI in toddlers at home, as an effort to prevent the condition from worsening. Therefore, it is expected that mothers increase their knowledge about ARI in toddlers.